Swath sonar bathymetry during R/V Heincke cruise HE478 with links to multibeam raw data files - Papenmeier, Svenja; Hass, H Christian (Alfred Wegener Institute - Wadden Sea Station Sylt, 2019)
Multibeam data were collected during R/V Heincke cruise HE478 with echo sounder system Kongsberg Simrad EM710. Data recording was executed along 92 parallel profiles in North Sea within German EEZ. Data are unprocessed and may contain outliers and blunders. Therefore the data should not directly be used for grid calculations and charting projects but need to be edited furthermore. One file contains a measurement period not exceeding 10 minutes. The dataset consists of 1473 files in Simrad Multibeam Processing Format which are compressed with GZIP (149.4 GB uncompressed). Simrad data files can be processed using the software packages CARIS HIPS/SIPS or with the open source software package MB-System (https://www.mbari.org/products/research-software/mb-system/).